Prolactin promotes transepithelial migration of lymphocytes through CCL2 - Liu, Peng; Zuo, Jinjiao; Lu, Hui; Zhang, Bin; Wu, Caihong (Poultry science, 2025)
The colostrum of sows contains a large number of lymphocytes originating from breast tissue. However, the mechanism of lymphocyte migration across the mammary epithelium remains unclear. Hormonal fluctuations during pregnancy are known to influence lymphocyte homing to the breast. In this study, we established a mammary epithelial cells (MECs)/T lymphocytes co-culture system to investigate the effects of colostral hormones on lymphocyte migration. Electron microscope and fluorescence-activated cell sorting results showed that the proportion of T lymphocytes in colostrum was about 9 %. Subsequently, the hormone concentration and number of T lymphocytes in colostrum were tested. The results revealed that there is a high content of prolactin and estrogen in colostrum, and the content of prolactin and estrogen is positively correlated with the number of T lymphocytes in colostrum. Furthermore, T lymphocytes were added to the upper ventricle in Transwell insert, and the estrogen and prolactin were added to the lower ventricle. The results showed that prolactin significantly promoted the T lymphocyte migration across the mammary epithelium, while estrogen had no effect. Finally, our study found that prolactin can promote the mammary epithelial cell to secrete CCL2 by Real-time quantitative PCR (RT-qPCR) and Enzyme-linked immunosorbent assay (ELISA). In order to further explore the transepithelial migration, a neutralizing antibody was applied to block CCL2. Results revealed that the migration of T lymphocytes across the breast epithelium was significantly inhibited after blocking CCL2. The above results showed that prolactin can promote the secretion of CCL2 by breast epithelial cells, and regulate the lymphocyte migration across the mammary epithelium into colostrum, and thereby may further improve lactogenic immunity in sows.